Rational Design of Envelope Identifies Broadly Neutralizing Human Monoclonal Antibodies to HIV-1 - Wu, Xueling; Yang, Zhi-Yong; Li, Yuxing; Hogerkorp, Carl-Magnus; Schief, William R; Seaman, Michael S; Zhou, Tongqing; Schmidt, Stephen D; Wu, Lan; Xu, Ling; Longo, Nancy S; McKee, Krisha; et al. (Science (American Association for the Advancement of Science), 2010)
Cross-reactive neutralizing antibodies (NAbs) are found in the sera of many HIV-1-infected individuals, but the virologic basis of their neutralization remains poorly understood. We used knowledge of HIV-1 envelope structure to develop antigenically resurfaced glycoproteins specific for the structurally conserved site of initial CD4 receptor binding. These probes were used to identify sera with NAbs to the CD4-binding site (CD4bs) and to isolate individual B cells from such an HIV-1-infected donor. By expressing immunoglobulin genes from individual cells, we identified three monoclonal antibodies, including a pair of somatic variants that neutralized over 90% of circulating HIV-1 isolates. Exceptionally broad HIV-1 neutralization can be achieved with individual antibodies targeted to the functionally conserved CD4bs of glycoprotein 120, an important insight for future HIV-1 vaccine design.